PROBLEMATIKA DAKWAH DI PRANCIS: SEBUAH ANALISIS KRITIS - Hakis, Hakis; Tajibu, Kamaluddin; Usman, Syahruni (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2024)
Abstract The aim of this research is to reveal the history of Islam in France, to examine the development of Islam in France and to analyze research into da'wah in France. This research is Library Research, a primary data source from online manuscripts, manuscripts, newspapers, magazines and related books. Using critical discourse analysis by dividing three dimensions of analysis, namely text, discourse practice, and socio-cultural practice. A critical operational approach was carried out using analytical techniques which were then developed into analysis. The results of the research show that the history of the arrival of Islam in France was in 721 AD when Abdurrahman al-Ghafiki's troops from the Umayyads expanded into France via the Pyrenean mountain route, master Septimenia and then entered the master Politiers and Tours near the city of Paris. Islam developed in France due to the arrival of many migrants from outside France from Islamic countries who had lived in France for a long time. According to the 1990 population calculations, there were 614,207 from Algeria, 575,652 from Morocco, 206,336 from Tunisia, and 197,712 from Turkey, then Muslim communities were formed and shows his existence as a Muslim. The problems of Islamic da'wah in France include that France is a secular state, religion has become an individual's privacy so it is difficult to detect their religion, then marginalization and prohibition on wearing the hijab as an identity for Muslim women, local residents are afraid of terrorism and fundamentalism makes Islam increasingly isolated. Key words: Immigrants, existence, marginalization